Exploring the promises of intersectionality for advancing women's health research - Clark Natalie; Varcoe Colleen; Cormier Renee; Reid Colleen; Hankivsky Olena; Benoit Cecilia; Brotman Shari (BMC, 2010)
Abstract Women's health research strives to make change. It seeks to produce knowledge that promotes action on the variety of factors that affect women's lives and their health. As part of this general movement, important strides have been made to raise awareness of the health effects of sex and gender. The resultant base of knowledge has been used to inform health research, policy, and practice. Increasingly, however, the need to pay better attention to the inequities among women that are caused by racism, colonialism, ethnocentrism, heterosexism, and able-bodism, is confronting feminist health researchers and activists. Researchers are seeking new conceptual frameworks that can transform the design of research to produce knowledge that captures how systems of discrimination or subordination overlap and "articulate" with one another. An emerging paradigm for women's health research is intersectionality. Intersectionality places an explicit focus on differences among groups and seeks to illuminate various interacting social factors that affect human lives, including social locations, health status, and quality of life. This paper will draw on recently emerging intersectionality research in the Canadian women's health context in order to explore the promises and practical challenges of the processes involved in applying an intersectionality paradigm. We begin with a brief overview of why the need for an intersectionality approach has emerged within the context of women's health research and introduce current thinking about how intersectionality can inform and transform health research more broadly. We then highlight novel Canadian research that is grappling with the challenges in addressing issues of difference and diversity. In the analysis of these examples, we focus on a largely uninvestigated aspect of intersectionality research - the challenges involved in the process of initiating and developing such projects and, in particular, the meaning and significance of social locations for researchers and participants who utilize an intersectionality approach. The examples highlighted in the paper represent important shifts in the health field, demonstrating the potential of intersectionality for examining the social context of women's lives, as well as developing methods which elucidate power, create new knowledge, and have the potential to inform appropriate action to bring about positive social change.